Visualization and quantification of NAD(H) in brain sections by a novel histo-enzymatic nitrotetrazolium blue staining technique - Balan, Irina S. (2009)
A histo-enzymatic technique for visualizing and quantifying endogenous NAD(H) in brain tissue was developed, based on coupled enzymatic cycling reactions that reduce nitrotetrazolium blue chloride to produce formazan. Conditions were used where the endogenous level of nicotinamide adenine dinucleotides (NAD(H)) was the rate limiting factor for formazan production. Spontaneous degradation of NAD(+) that occurs during incubation of thawed tissue was minimized by the addition of nicotinamide mononucleotide, an inhibitor of NAD(+) glycohydrolases. Cryostat sections of brains obtained from rats immediately after decapitation and at 30 min later were used to determine the effects of ischemia alone on brain NAD(H) levels and neuroanatomic distribution. The ischemic insult resulted in a greater than 50% decline in the rate of formazan generation in the CA1 pyramidal neuronal layer of the hippocampus and in the parietal cortex and striatum, but not in the CA3 and dentate gyrus (DG) subregions of the hippocampus. The ischemia-induced changes in NAD(H) levels were confirmed by utilizing spectrofluorimetric measurements of NAD(H) present in perchloric acid extracts of brain samples. This new histo-enzymatic technique is suitable for visualizing and quantifying relative NAD(H) levels in the brain. This assay could prove useful in identifying region-selective NAD(H) catabolism that may contribute to neurodegeneration.